Intra and Interfaith Dialogue and Peace Building A Muslim Personal Story - Muhammad Shafiq (حقوق بشر)
The word dialogue comes from the Greek word ‘dialogos’ and is commonly used in the meaning of conversation between two people, two groups and/or communities or organizations. Dialogue is not a debate to win or lose or to convince the other of a particular way of thinking. Dialogue is communicative conversation that involves intensely creative process with a goal to create peaceful and respectful relations among participants and in a community. When religious communities or organizations nominate a representative to participate in the intra or interfaith dialogue, they make sure that their nominees are trained in the art of dialogue. First, that he/she represents the community and second, that if he/she is not trained in the art of dialogue they understand that there may be a negative impact on the intra-faith or interfaith dialogue. For a healthy intra-faith and interfaith dialogue, the organization or community representatives must be trained in rights, responsibilities and skills of dialogue. This paper will discuss some of those rights, responsibilities and skills essential for a successful dialogue in the light of those principles and guidelines initiated in the Qur’an and Sunnah.